2006
DOI: 10.1255/ejms.814
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix-Assisted Laser Desorption/Ionization Compatible Reagent for Tagging Tryptophan Residues

Abstract: Chemical tagging of amino acids is an important tool in proteomics analysis, and has been used to introduce isotope labels and mass defect labels into proteolytic peptides by derivatization of cysteine or lysine residues. Here, we present a new reagent with chemical specificity for tryptophan residues. Previously, 2-nitrobenzenesulfenyl chloride has been used as a highly specific reagent for labeling tryptophan residues. We show that this tag undergoes UV dissociation during matrix assisted laser desorption/io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compounds like 2-nitro-and 2,4-dinitrophenylsulfenylchloride reacting at the 2-position of the indole group can be used for studying active sites of enzymes (13). Applications in the field of proteomics, including relative quantification studies employing stable isotope-labeled analogues, were reported (14)(15)(16); N-bromosuccinimide is a derivatizing reagent used for similar applications (17). Another method, selectively targeting the indole nitrogen, uses rhodium carbenoids for the derivatization of tryptophan residues in proteins as recently reported by Antos et al (18).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds like 2-nitro-and 2,4-dinitrophenylsulfenylchloride reacting at the 2-position of the indole group can be used for studying active sites of enzymes (13). Applications in the field of proteomics, including relative quantification studies employing stable isotope-labeled analogues, were reported (14)(15)(16); N-bromosuccinimide is a derivatizing reagent used for similar applications (17). Another method, selectively targeting the indole nitrogen, uses rhodium carbenoids for the derivatization of tryptophan residues in proteins as recently reported by Antos et al (18).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3D cultures are less costly and labor-intensive than animal studies and should be prioritized at a preliminary stage. Experimental data show that the pattern of gene expression, mRNA splicing, intracellular signaling, cytoskeletal organization and secretion profile of cells grown in 3D cultures more closely resemble what is observed in vivo than when grown in two-dimensional (2D) cultures 84-88 .…”
Section: Challenges and Perspectives For The P19arf + Ifn{\tf="greek_mentioning
confidence: 82%
“…[25][26] 2-(Trifluoromethyl)benzenesulfenyl chloride as an alternative tagging reagent has been introduced by Amster and coworkers. 27 Several other (more or less) selective tryptophan modification agents are known, like N-bromosuccinimide, 28 2-hydroxy-5-nitrobenzyl bromide, 29 or rhodium carbenoids, 30 but they have not been applied to proteomic samples. A kit for the enrichment of tryptophan containing peptides has been made commercially available, 31 but to our knowledge, no application has been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To isolate the tagged peptides, the increased hydrophobicity upon modification of tryptophan residues was utilized. Recently, an improved enrichment strategy using a phenyl column and the application to biological samples have been described. 2-(Trifluoromethyl)benzenesulfenyl chloride as an alternative tagging reagent has been introduced by Amster and co-workers . Several other (more or less) selective tryptophan modification agents are known, like N -bromosuccinimide, 2-hydroxy-5-nitrobenzyl bromide, or rhodium carbenoids, but they have not been applied to proteomic samples.…”
Section: Introductionmentioning
confidence: 99%